Efektivitas Problem Based Learning Terhadap Peningkatan Hasil Belajar Matematika Materi Perpangkatan Dua Fase B - Aji, Andri Banu; Patonah, Siti; Suyatmi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The teaching of mathematics in primary schools frequently encounters challenges in raising pupils' academic performance, particularly in the cognitive area. Using Papada media, the PBL Learning Model is being used to address this issue. seeks to assess how well the PBL learning model—which is aided by Papada media—improves second-level mathematics learning results at Stage B SD Supriyadi 02 Semarang. A one-group pretest-posttest research design with experimental methodologies and a quantitative methodology were employed in the study. 28 students from SD Supriyadi 02 Semarang's class IV B made up the research sample, and a multiple-choice exam was employed to gather data. The outcomes of the paired sample t data analysis with a significance level of 0.001, which is less than 0.05, the test revealed a substantial increase in student learning outcomes following the implementation of the therapy, supporting the acceptance of the alternative hypothesis (H1) and the rejection of the null hypothesis (H0). These results suggest that the PBL Learning Model, which is backed by Papada Media, is useful for enhancing mathematics learning outcomes, particularly for the two-phase B level curriculum at SD Supriyadi 02 Semarang.